High-hardness coated cutting tool and preparation method thereof

By depositing TiAlN/TiN and CrAlN/TiAlN composite coatings on the surface of the tool substrate and optimizing the processing parameters, the problem of TiAlN coating sticking to the tool when cutting nickel-containing stainless steel was solved, the hardness and wear resistance were improved, and the service life of the tool was extended.

CN120700440APending Publication Date: 2025-09-26JIANGSU TIANGONG CEMENTED CARBIDE TECH CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510690797.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-26
Publication Date
2025-09-26

AI Technical Summary

Technical Problem

TiAlN coatings tend to stick to the tool when cutting nickel-containing stainless steel, have a high friction coefficient, and cannot meet industrial needs. The cutting performance and service life need to be improved.

Method used

A TiN bonding layer, a TiAlN/TiN transition layer, a CrAlN/TiAlN transition layer, and a CrAlN top layer are sequentially deposited on the substrate surface. The substrate is pretreated by laser treatment and hydrogen reduction treatment, and deposition parameters such as power density, gas flow rate, and bias voltage are optimized.

Benefits of technology

It improves the hardness and wear resistance of the coating, strengthens the bonding force of the tool, extends its service life, and reduces the wear of the tool tip.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005421861460000071
    Figure BDA0005421861460000071
  • Figure BDA0005421861460000072
    Figure BDA0005421861460000072
  • Figure BDA0005421861460000081
    Figure BDA0005421861460000081
Patent Text Reader

Abstract

The invention relates to the technical field of coated cutting tools, in particular to a high-hardness coated cutting tool and a preparation method thereof. The high-hardness coated cutting tool comprises a TiN bonding layer, a TiAlN / TiN transition layer, a CrAlN / TiAlN transition layer and a CrAlN top layer which are sequentially arranged on the surface of a base body from inside to outside. Before the iN bonding layer is deposited, the substrate needs to be subjected to laser treatment and hydrogen reduction treatment; the high-hardness T coating cutter has excellent hardness, wear resistance and binding force, the service life of the coating is long, and the high-hardness T coating cutter can be applied to cutting work for a long time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of coated cutting tools, in particular to a high-hardness coated cutting tool and a preparation method thereof. Background Art

[0002] With the development of the manufacturing industry, people have put forward higher requirements on the performance of cutting tools. Coating cutting tools is one of the important ways to improve cutting tool performance. Cutting tools with deposited coatings can improve processing efficiency and processing accuracy, extend tool life and reduce processing costs.

[0003] TiAlN coating is made by adding Al element to TiN, which greatly improves the hardness and oxidation resistance of the original coating. However, at the same time, the friction of TiAlN coating becomes higher at around 0.8, and the tool will stick when cutting nickel-containing stainless steel, which cannot meet industrial needs and greatly restricts the promotion and application of TiAlN coating.

[0004] Patent document CN112831752A discloses a method for preparing a C-doped TiAlN coating, comprising a gradient composite coating of Ti, TiN, TiAlN, and TiAlCN. This coating exhibits a coefficient of friction between 0.25 and 0.35, a hardness between 2800 and 3500 HV, and excellent corrosion resistance. It has promising market applications in cutting tools, molds, aerospace, automotive parts, and other industries. However, its cutting performance and service life still need to be further improved. Summary of the Invention

[0005] In view of this, the object of the present invention is to provide a high-hardness coated tool and a preparation method thereof, so as to provide a coated tool with high hardness and a long service life.

[0006] Based on the above objectives, the present invention provides a high-hardness coated tool, comprising a TiN bonding layer, a TiAlN / TiN transition layer, a CrAlN / TiAlN transition layer, and a CrAlN top layer, which are sequentially arranged on the surface of a substrate from the inside out; before depositing the TiN bonding layer, the substrate needs to be laser treated and hydrogen reduced;

[0007] Furthermore, the present invention also provides a method for preparing a high-hardness TiAl coated tool, the specific steps of which are as follows:

[0008] S1: The substrate is cleaned, and then subjected to laser treatment and hydrogen reduction treatment to obtain a substrate to be deposited;

[0009] S2: depositing a TiN bonding layer on the surface of the substrate to be deposited;

[0010] S3: depositing a TiAlN / TiN transition layer on the surface of the TiN bonding layer;

[0011] S4: depositing a CrAlN / TiAlN transition layer on the surface of the TiAlN / TiN transition layer;

[0012] S5: depositing a CrAlN top layer on the surface of the CrAlN / TiAlN transition layer;

[0013] Preferably, the process parameters of the laser treatment in step S1 are as follows: wavelength 1064 nm, power density 15-25 J / cm 2 .

[0014] Preferably, the process parameters of the hydrogen reduction treatment in step S1 are as follows: a mixed gas of hydrogen and argon (hydrogen accounts for 30% by volume) is introduced into a vacuum furnace at a temperature of 400-500° C. for 30-60 minutes.

[0015] Preferably, the process parameters for depositing the TiN bonding layer in step S2 are as follows: nitrogen flow rate is 800-950 sccm, chamber pressure is 2-5 Pa, Ti target current is 100-150 A, workpiece support bias is -80 to -120 V, and deposition time is 30-90 min.

[0016] Preferably, the process parameters for depositing the TiAlN / TiN transition layer in step S3 are as follows: nitrogen flow rate is 800-950 sccm, chamber pressure is 2-5 Pa, TiAl target current is 100-150 A, Ti target current is 130-180 A, workpiece support bias is -100 to -140 V, and deposition time is 5-15 min.

[0017] Preferably, the process parameters for depositing the CrAlN / TiAlN transition layer in step S4 are as follows: nitrogen flow rate is 800-950 sccm, chamber pressure is 2-5 Pa, CrAl target current is 100-150 A, TiAl target current is 130-180 A, workpiece support bias is -100 to -140 V, and deposition time is 5-15 min.

[0018] Preferably, the process parameters for depositing the CrAlN top layer in step S5 are as follows: nitrogen flow rate of 800-950 sccm, chamber pressure of 2-5 Pa, CrAl target current of 130-180 A, workpiece support bias of -140 to -180 V, and deposition time of 90-150 min.

[0019] Preferably, the thickness of the TiN bonding layer is 0.5-1.5 μm; the thickness of the TiAlN / TiN transition layer is 0.2-0.5 μm; the thickness of the CrAlN / TiAlN transition layer is 0.2-0.5 μm; and the thickness of the CrAlN top layer is 1.5-2.5 μm.

[0020] Beneficial effects of the present invention: The high-hardness coated cutting tool of the present invention has excellent hardness, wear resistance and bonding strength, and the coating has a long life and can be used for cutting work for a long time.

[0021] The present invention deposits TiAlN / TiN and CrAlN / TiAlN composite coatings on the surface of the tool substrate, which has a certain buffering effect, effectively reduces the wear of the tool tip, can improve the comprehensive performance of the coating, and can effectively increase the service life of the tool. DETAILED DESCRIPTION

[0022] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below with reference to specific embodiments.

[0023] Example 1: (1) The tool substrate was ultrasonically cleaned in acetone and alcohol, and then cleaned with deionized water for 20 minutes. Then, the substrate was scanned with a pulsed fiber laser in an argon atmosphere. The laser wavelength was 1064 nm and the power density was 15 J / cm 2 After the treatment is completed, it is placed in a vacuum furnace, and a mixed gas of hydrogen and argon (hydrogen accounts for 30% by volume) is introduced, and maintained at 400°C for 30 minutes to obtain a substrate to be deposited;

[0024] (2) Place the substrate to be deposited into the chamber of the vacuum coating machine and adjust the vacuum degree of the equipment to 8×10 -5 mbar, heated to 470 ° C, introduced nitrogen, nitrogen flow rate of 800 sccm, chamber pressure of 2 Pa, opened the Ti target, Ti target current of 100 A, workpiece support bias voltage of -80 V, deposition time of 30 min;

[0025] (3) Keeping the deposition atmosphere unchanged, the TiAl target and the Ti target were ignited simultaneously. The TiAl target current was 100 A, the Ti target current was 130 A, the workpiece support bias was -100 V, and the deposition time was 5 min.

[0026] (4) Keeping the deposition atmosphere unchanged, the Ti target is turned off, and the CrAl target and TiAl target are ignited at the same time. The CrAl target current is 100 A, the TiAl target current is 130 A, the workpiece support bias is -100 V, and the deposition time is 5 min.

[0027] (5) Keep the deposition atmosphere unchanged, turn off the TiAl target, the CrAl target current is 130A, the workpiece holder bias is -140V, and the deposition time is 90min. After the deposition is completed, turn off the CrAl target and bias, turn off the heating, turn off the nitrogen, and take out the substrate when the chamber temperature drops to room temperature to obtain a high-hardness coated tool.

[0028] Example 2: (1) The tool substrate was ultrasonically cleaned in acetone and alcohol, and then rinsed with deionized water for 20 minutes. Then, the substrate was scanned using a pulsed fiber laser in an argon atmosphere. The laser wavelength was 1064 nm and the power density was 20 J / cm 2 After the treatment is completed, it is placed in a vacuum furnace, and a mixed gas of hydrogen and argon (hydrogen accounts for 30% by volume) is introduced, and maintained at 450°C for 50 minutes to obtain a substrate to be deposited;

[0029] (2) Place the substrate to be deposited into the chamber of the vacuum coating machine and adjust the vacuum degree of the equipment to 8×10 -5 mbar, heated to 475 ° C, introduced nitrogen, nitrogen flow rate of 850 sccm, chamber pressure of 4 Pa, opened the Ti target, Ti target current of 130 A, workpiece support bias voltage of -100 V, deposition time of 60 min;

[0030] (3) Keeping the deposition atmosphere unchanged, the TiAl target and the Ti target were ignited simultaneously. The TiAl target current was 130 A, the Ti target current was 150 A, the workpiece support bias voltage was -120 V, and the deposition time was 10 min.

[0031] (4) Keeping the deposition atmosphere unchanged, the Ti target is turned off, and the CrAl target and TiAl target are ignited at the same time. The CrAl target current is 130 A, the TiAl target current is 150 A, the workpiece support bias is -120 V, and the deposition time is 10 min.

[0032] (5) Keep the deposition atmosphere unchanged, turn off the TiAl target, the CrAl target current is 150A, the workpiece holder bias is -150V, and the deposition time is 120min. After the deposition is completed, turn off the CrAl target and bias, turn off the heating, turn off the nitrogen, and take out the substrate when the chamber temperature drops to room temperature to obtain a high-hardness coated tool.

[0033] Example 3: (1) The tool substrate was ultrasonically cleaned in acetone and alcohol, and then rinsed with deionized water for 20 minutes. Then, the substrate was scanned by a pulsed fiber laser in an argon atmosphere, wherein the laser wavelength was 1064 nm and the power density was 25 J / cm 2 After the treatment is completed, the substrate is placed in a vacuum furnace, and a mixed gas of hydrogen and argon (hydrogen accounts for 30% by volume) is introduced, and maintained at 500° C. for 60 minutes to obtain a substrate to be deposited;

[0034] (2) Place the substrate to be deposited into the chamber of the vacuum coating machine and adjust the vacuum degree of the equipment to 8×10 -5mbar, heated to 480°C, introduced nitrogen with a nitrogen flow rate of 950 sccm, chamber pressure of 5 Pa, opened the Ti target, Ti target current of 150 A, workpiece holder bias voltage of -120 V, and deposition time of 90 min;

[0035] (3) Keeping the deposition atmosphere unchanged, the TiAl target and the Ti target were ignited simultaneously. The TiAl target current was 150 A, the Ti target current was 180 A, the workpiece support bias was -140 V, and the deposition time was 15 min.

[0036] (4) Keeping the deposition atmosphere unchanged, the Ti target is turned off, and the CrAl target and TiAl target are ignited at the same time. The CrAl target current is 150 A, the TiAl target current is 180 A, the workpiece support bias is -140 V, and the deposition time is 15 min.

[0037] (5) Keeping the deposition atmosphere unchanged, the TiAl target is turned off, the CrAl target current is 180A, the workpiece holder bias is -180V, and the deposition time is 150min. After the deposition is completed, the CrAl target and bias are turned off, the heating is turned off, and the nitrogen is turned off. When the chamber temperature drops to room temperature, the substrate is taken out to obtain a high-hardness coated tool.

[0038] Comparative Example 1: (1) The tool substrate was ultrasonically cleaned in acetone and alcohol, and then cleaned with deionized water for 20 minutes. Then, the substrate was scanned using a pulsed fiber laser in an argon atmosphere, wherein the laser wavelength was 1064 nm and the power density was 20 J / cm 2 After the treatment is completed, it is placed in a vacuum furnace, and a mixed gas of hydrogen and argon (hydrogen accounts for 30% by volume) is introduced, and maintained at 450°C for 50 minutes to obtain a substrate to be deposited;

[0039] (2) Place the substrate to be deposited into the chamber of the vacuum coating machine and adjust the vacuum degree of the equipment to 8×10 -5 mbar, heated to 475 ° C, introduced nitrogen, nitrogen flow rate of 850 sccm, chamber pressure of 4 Pa, opened the Ti target, Ti target current of 130 A, workpiece support bias voltage of -100 V, deposition time of 60 min;

[0040] (3) Keeping the deposition atmosphere unchanged, ignite the TiAl target, turn off the Ti target, set the TiAl target current to 130 A, the workpiece support bias to -120 V, and the deposition time to 10 min;

[0041] (4) Keeping the deposition atmosphere unchanged, ignite the CrAl target and the TiAl target, the CrAl target current is 130A, the TiAl target current is 150A, the workpiece support bias voltage is -120V, and the deposition time is 10min;

[0042] (5) Keep the deposition atmosphere unchanged, turn off the TiAl target, the CrAl target current is 150A, the workpiece holder bias is -150V, and the deposition time is 120min. After the deposition is completed, turn off the CrAl target and bias, turn off the heating, turn off the nitrogen, and take out the substrate when the chamber temperature drops to room temperature to obtain a high-hardness coated tool.

[0043] Comparative Example 2: (1) The tool substrate was ultrasonically cleaned in acetone and alcohol, and then rinsed with deionized water for 20 minutes. Then, the substrate was scanned using a pulsed fiber laser in an argon atmosphere. The laser wavelength was 1064 nm and the power density was 20 J / cm 2 After the treatment is completed, it is placed in a vacuum furnace, and a mixed gas of hydrogen and argon (hydrogen accounts for 30% by volume) is introduced, and maintained at 450°C for 50 minutes to obtain a substrate to be deposited;

[0044] (2) Place the substrate to be deposited into the chamber of the vacuum coating machine and adjust the vacuum degree of the equipment to 8×10 -5 mbar, heated to 475 ° C, introduced nitrogen, nitrogen flow rate of 850 sccm, chamber pressure of 4 Pa, opened the Ti target, Ti target current of 130 A, workpiece support bias voltage of -100 V, deposition time of 60 min;

[0045] (3) Keeping the deposition atmosphere unchanged, the TiAl target and the Ti target were ignited simultaneously. The TiAl target current was 130 A, the Ti target current was 150 A, the workpiece support bias voltage was -120 V, and the deposition time was 10 min.

[0046] (4) Keeping the deposition atmosphere unchanged, the Ti target and TiAl target were turned off, and the CrAl target was ignited. The CrAl target current was 130 A, the workpiece support bias was -120 V, and the deposition time was 10 min.

[0047] (5) Keep the deposition atmosphere unchanged, the CrAl target current is 150A, the workpiece support bias is -150V, and the deposition time is 120min. After the deposition is completed, turn off the CrAl target and bias, turn off the heating, turn off the nitrogen, and take out the substrate when the chamber temperature drops to room temperature to obtain a high-hardness coated tool.

[0048] Comparative Example 3: (1) The tool substrate was ultrasonically cleaned in acetone and alcohol, and then cleaned with deionized water for 20 minutes. Then, the substrate was scanned using a pulsed fiber laser in an argon atmosphere. The laser wavelength was 1064 nm and the power density was 20 J / cm 2After the treatment is completed, it is placed in a vacuum furnace, and a mixed gas of hydrogen and argon (hydrogen accounts for 30% by volume) is introduced, and maintained at 450°C for 50 minutes to obtain a substrate to be deposited;

[0049] (2) Place the substrate to be deposited into the chamber of the vacuum coating machine and adjust the vacuum degree of the equipment to 8×10 -5 mbar, heated to 475 ° C, introduced nitrogen, nitrogen flow rate of 850 sccm, chamber pressure of 4 Pa, opened the Ti target, Ti target current of 130 A, workpiece support bias voltage of -100 V, deposition time of 60 min;

[0050] (3) Keeping the deposition atmosphere unchanged, ignite the TiAl target, turn off the Ti target, set the TiAl target current to 130 A, the workpiece support bias to -120 V, and the deposition time to 10 min;

[0051] (4) Keeping the deposition atmosphere unchanged, ignite the CrAl target, turn off the TiAl target, set the CrAl target current to 130 A, the workpiece support bias to -120 V, and the deposition time to 10 min;

[0052] (5) Keep the deposition atmosphere unchanged, the CrAl target current is 150A, the workpiece support bias is -150V, and the deposition time is 120min. After the deposition is completed, turn off the CrAl target and bias, turn off the heating, turn off the nitrogen, and take out the substrate when the chamber temperature drops to room temperature to obtain a high-hardness coated tool.

[0053] Performance Testing

[0054] Hardness: Tested using a nanoindenter:

[0055] Friction and wear test: Use CSM HT-1000 ball-on-disc high-temperature friction and wear tester for testing. The following formula is used to calculate the coating wear rate:

[0056]

[0057] Where, K is the wear rate; Wv is the total wear volume, mm 3 ; L-loading force, N; S-wear scar circumference, mm; d-number of turns.

[0058] Adhesion: A large load scratch tester is used to test the adhesion of the coating.

[0059] Table 1 Performance test results

[0060]

[0061]

[0062] Data analysis: It can be seen from the examples in Table 1 that the high-hardness coated cutting tools of the present invention have excellent hardness, wear resistance and bonding strength, and the coating has a long life and can be used for cutting work for a long time.

[0063] It can be seen from Example 2 and Comparative Examples 1-3 in Table 1 that the composite coating of Example 2 of the present invention is superior to Comparative Examples 1-3 in terms of hardness, wear resistance and coating adhesion. This fully demonstrates that by depositing TiAlN / TiN and CrAlN / TiAlN composite coatings on the surface of the tool substrate, a certain buffering effect is achieved, which effectively reduces the wear of the tool tip, improves the comprehensive performance of the coating, and effectively increases the service life of the tool.

[0064] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Within the scope of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.

Claims

1. A high hardness coating tool, characterized in that: The method comprises a TiN bonding layer, a TiAlN / TiN transition layer, a CrAlN / TiAlN transition layer and a CrAlN top layer which are sequentially arranged on the surface of the substrate from the inside to the outside. Before depositing the TiN bonding layer, the substrate needs to be subjected to laser treatment and hydrogen reduction treatment.

2. A method for preparing a high-hardness coated cutting tool according to claim 1, characterized in that: The specific steps are as follows: S1: The substrate is cleaned, and then subjected to laser treatment and hydrogen reduction treatment to obtain a substrate to be deposited; S2: depositing a TiN bonding layer on the surface of the substrate to be deposited; S3: depositing a TiAlN / TiN transition layer on the surface of the TiN bonding layer; S4: depositing a CrAlN / TiAlN transition layer on the surface of the TiAlN / TiN transition layer; S5: depositing a CrAlN top layer on the surface of the CrAlN / TiAlN transition layer.

3. The preparation method according to claim 2, characterized in that The process parameters of the laser treatment in step S1 are as follows: wavelength 1064nm, power density 15-25J / cm 2 .

4. The preparation method according to claim 2, characterized in that The process parameters of the hydrogen reduction treatment in step S1 are as follows: a mixed gas of hydrogen and argon (hydrogen accounts for 30% by volume) is introduced into a vacuum furnace at a temperature of 400-500° C. for 30-60 minutes.

5. The preparation method according to claim 2, characterized in that The process parameters for depositing the TiN bonding layer in step S2 are as follows: nitrogen flow rate of 800-950 sccm, chamber pressure of 2-5 Pa, Ti target current of 100-150 A, workpiece support bias of -80 to -120 V, and deposition time of 30-90 min.

6. The preparation method according to claim 2, characterized in that The process parameters for depositing the TiAlN / TiN transition layer in step S3 are as follows: nitrogen flow rate is 800-950 sccm, chamber pressure is 2-5 Pa, TiAl target current is 100-150 A, Ti target current is 130-180 A, workpiece support bias is -100 to -140 V, and deposition time is 5-15 min.

7. The preparation method according to claim 2, characterized in that The process parameters for depositing the CrAlN / TiAlN transition layer in step S4 are as follows: nitrogen flow rate of 800-950 sccm, chamber pressure of 2-5 Pa, CrAl target current of 100-150 A, TiAl target current of 130-180 A, workpiece support bias of -100 to -140 V, and deposition time of 5-15 min.

8. The preparation method according to claim 2, characterized in that The process parameters for depositing the CrAlN top layer in step S5 are as follows: nitrogen flow rate of 800-950 sccm, chamber pressure of 2-5 Pa, CrAl target current of 130-180 A, workpiece support bias of -140 to -180 V, and deposition time of 90-150 min.

9. The preparation method according to claim 2, characterized in that The thickness of the TiN bonding layer is 0.5-1.5 μm; the thickness of the TiAlN / TiN transition layer is 0.2-0.5 μm; the thickness of the CrAlN / TiAlN transition layer is 0.2-0.5 μm; and the thickness of the CrAlN top layer is 1.5-2.5 μm.

Citation Information

Patent Citations

  • Preparation method of C-doped TiAlN coating

    CN112831752A